Riemannian Metrics with large lambda(1) - Colbois, Bruno; Dodziuk, Jozef (My University, 1994)
We show that every compact smooth manifold of three or more dimensions carries a Riemannian metric of volume one and arbitrarily large first eigenvalue of the Laplacian.
Keywords: LAPLACIAN; SPECTRUM